Analytical method for load response of a transmission line in a double-enclosure with multiple covered apertures. Issue 11 (13th August 2017) - Hao, Jianhong; Jiang, Luhang; Gong, Yanfei; Fan, Jieqing
Abstract: An efficient analytical model has been developed for predicting the load response of a lossless transmission line (TL) in a rectangular double-enclosure with multiple apertures covered by conductive sheets, excited by an external plane wave of oblique incidence. First, the electromagnetic field in the enclosure is calculated using the enclosure dyadic Green's function and the transfer impedance of the sheets against the plane wave. Then, the electric current induced at the termination loads of the TL is computed in combination of the equivalent lumped-pi circuit model of the line and the Agrawal's model. The analytical model has been successfully verified by the full-wave software CST (Computer Simulation Technology) over a wide frequency band, and it is employed to analyze the effect of various parameters on the induced current, including the sheet conductivity, the load impedance, and the position of the line. This model consumes less time compared with numerical methods, and it can also deal with covered aperture arrays on multiple sides of the enclosure.